Introduction: Patrick Modiano's Dora Bruder - Richard J. Golsan; Lynn A. Higgins (Studies in 20th & 21st Century Literature, 2007)
After establishing a reputation as a literary enfant terrible in the late 1960s and early 1970s, Patrick Modiano is now firmly ensconced as a Grand Old Man (perhaps the Grand Old Man) of French letters and arguably as France's greatest living novelist…
Keywords: enfant; literary enfant terrible; Patrick Modiano; Grand Old Man; letter; letters; French novel; French novelist